Nickel ferrite nanoparticles‐doped graphene oxide as a heterogeneous Fenton catalyst: Synthesis, characterization, and catalytic application. Issue 4 (19th July 2022) - Thy, Lu Thi Mong; Tuyen, Nguyen Ngoc Kim; Viet, Nguyen Duc; Huong, Le Minh; Tinh, Ninh Thi; Lin, Tong Hoang; Son, Nguyen Truong; Oanh, Doan Thi Yen; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, nickel ferrite nanoparticles‐doped graphene oxide nanocomposite (NiFe2 O4 /GO or NG) was fabricated by impregnation method with five different mass ratios of NiFe2 O4 :GO, namely, 1:1, 3:7, 4:6, 7:3, and 6:4, corresponding to NG1, NG2, NG3, NG4, and NG5 samples. According to the catalytic efficiency of the Fenton reaction of methylene blue (MB), the NG3 sample was chosen as the most appropriate sample, which possessed the highest catalytic efficiency. The effects of volume of H2 O2, reaction time, and MB concentration, on the catalytic efficiency of NG3, were also investigated. The results revealed that with the 0.5 mL H2 O2, MB concentration of 150 mg/L, and 60 min, the NG3 sample exhibited the highest catalytic efficiency of more than 99 %. The characterization of NG3 was investigated by advanced analysis methods. The results indicated that NiFe2 O4 possessed a sphere shape with the size of 10‐30 nm, which was uniformly distributed on the GO sheets. Additionally, NG3 possessed a high specific surface area and magnetism. The above results confirmed that NiFe2 O4 /GO can be potentially applied in the treatment of organic dyes in water. Abstract :